1998
DOI: 10.1021/jp9804401
|View full text |Cite
|
Sign up to set email alerts
|

C60·Bromobenzene Solvate:  Crystallographic and Thermochemical Studies and Their Relationship to C60 Solubility in Bromobenzene

Abstract: Differential scanning calorimetry, solution calorimetry, and room-temperature single-crystal X-ray diffraction were used to study the thermodynamic and structural properties of a solvated crystal C60·2C6H5Br. In the monoclinic solvate, two orientations of C60 were observed with fractional populations of 0.71 and 0.29. The enthalpy of solution of pure C60 in bromobenzene was determined to be Δsol H[C60(s)] = −11.5 ± 2.0 kJ/mol. The enthalpy of solution of the solvated crystal was Δsol H[C60·2C6H5Br(s)] = +28 ± … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
52
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(56 citation statements)
references
References 15 publications
4
52
0
Order By: Relevance
“…Nonetheless, there are several reports in the literature, where it was demonstrated that the solubility of fullerene-based compounds depends on the composition, the crystal structure, and the thermodynamic stability of ''solvates'' that are formed in the system. [31][32][33][34] Solvates are Van der Waals adducts of solutes (dissolved compounds) with solvents. In the simplest case, solubility is determined by the equilibrium of the system schematically outlined in Scheme 2, where ''S'' denotes the solvent molecules.…”
Section: Solubility Of the Fullerene Derivativesmentioning
confidence: 99%
“…Nonetheless, there are several reports in the literature, where it was demonstrated that the solubility of fullerene-based compounds depends on the composition, the crystal structure, and the thermodynamic stability of ''solvates'' that are formed in the system. [31][32][33][34] Solvates are Van der Waals adducts of solutes (dissolved compounds) with solvents. In the simplest case, solubility is determined by the equilibrium of the system schematically outlined in Scheme 2, where ''S'' denotes the solvent molecules.…”
Section: Solubility Of the Fullerene Derivativesmentioning
confidence: 99%
“…fullerenes of a single size. We probed models of all sizes that were, to our knowledge, resolved, hence with available structural coordinates: C60 [19], C70 [20], C74 [21], C76 [22], C80 [23], C82 [24], C84 [25], C90 [26], C96 [27]. Furthermore, a simulation with the hypothesized structure of fullerene C180 [28] was made, using the cartesian coordinates published in the webpage http://www.nanotube.msu.edu/fullerene/fullerene-isomers.html.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…2), the solubility polytherm is an S-shaped curve; this is evidence that the solid phase at equilibrium with the saturated solution is nonsolvated ë 70 fullerene (otherwise, a nonmonotonic temperature dependence of solubility is as a rule observed [8][9][10][11][12]). The absence of crystallization styrene in the solid phase with pure fullerene ë 70 was also proved experimentally.…”
Section: Introductionmentioning
confidence: 97%